Pengaruh Kualitas Produk, Voucher Diskon dan Shopping Lifestyle Terhadap Keputusan Pembelian yang Dimediasi oleh Electronic Word Of Mouth Pada Live Streaming Shopee (Study pada Mahasiswa di Daerah Istimewa Yogyakarta): (Study pada Mahasiswa di DIY) - Wahyuningsih, Istiana; Damayanti, Dila (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Using E-WOM as a mediator, this study sought to determine the impact of product quality, discount coupons, and shopping habits on consumers' final purchase choices. This study employs a qualitative technique to provide a descriptive account. Student body of Daerah Istimewa Yogyakarta that has used Shopee for live streaming purchases. One hundred respondents made up the sample that was determined using the Solvin formula. Samples are collected using purposive sampling, a non-probability sampling approach, in accordance with predetermined criteria. Specifically, PLS in conjunction with the SmartPLS 4.0 software is used for data analysis. This study's findings indicate that product quality influences electronic word of mouth and purchase decisions in a positive but insignificant way, while discount vouchers influence electronic word of mouth in a positive and significant way but purchase decisions in a positive but insignificant way. When it comes to electronic word of mouth, Shopping Lifestyle is neutral or somewhat negative, but when it comes to purchase choices, it's positively and significantly influential. Product quality, discount coupons, and buying habits are the three factors that electronic word of mouth cannot influence.